THEME: INTEGRATING TECHNOLOGY IN INTENSIVE LANGUAGE TEACHING - Safarova Dildora,; Tursunova Mahliyo, (Ustozlar uchun, 2025)
This article explores the integration of technology in intensive language teaching, highlighting the benefits of digital tools in accelerating language acquisition. It discusses the role of artificial intelligence, virtual reality, mobile applications, and speech recognition technology in creating an interactive and immersive learning environment. Additionally, the article examines the impact of online collaboration platforms and gamification on learner engagement and motivation. While technology enhances personalized learning and accessibility, the importance of balancing digital tools with traditional teaching methods is emphasized. The article also addresses challenges such as the digital divide and the need for teacher training to ensure effective implementation. By leveraging technological advancements, educators can create more efficient and engaging intensive language programs that support rapid and effective language learning.